ANALYSIS OF INFLUENCE OF LUBRICATING GAS ON STATIC CHARACTERISTICS OF THE FOIL HYDRODYNAMIC THRUST GAS BEARING - LU Pan; QIANG Meng; JIN Wen; ZHOU Quan (Jixie qiangdu)
Taking the new type of protuberant foil hydrodynamic thrust gas bearing as the research object,the finite element method and the Newton-Raphson iterative method are used to solve the numerical model of fluid-solid coupling by MATLAB software. The film pressure distribution,the thickness distribution and the carrying capacity of the bearing under different temperature of the same lubricating gas and the same lubricating gas at different temperatures were obtained. And the influence of the physical properties of the lubricating gas on the static characteristics of the foil dynamic pressure thrust bearing in the aircraft turbo cooler is studied. The results show that the lubricating gas with large dynamic viscosity has a large gas film pressure and thickness distribution,and the higher carrying capacity. With the high temperature of the bearing running at high speed for a long time,the change of the physical parameters of the lubricating gas is conducive to improving the carrying capacity.